1967
DOI: 10.1002/pssb.19670210222
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Diffraction Contrast on Ferromagnetic Domain Walls in Fe‐Si Single Crystals

Abstract: The contrast of ferromagnetic domains in (001) Fe-304 Si single crystal plates is studied using X-ray diffraction topography. This contrast is found to be due solely to the difference in deformation on opposite sides of the wall which is produced by magnetostriction. 180' walls are therefore never visible, whereas 90' walls show contrast if diffracting planes not belonging to the zone m,nil are used (m, and m, are unit vectors parallel t o the magnetization on the two sides of the wall). Der Kontrast von ferro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1971
1971
1998
1998

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Consequently, the zig-zag wall must be invisible. This result is in agreement with the extinction rule of Polcarova et al [18].…”
Section: I-supporting
confidence: 93%
See 1 more Smart Citation
“…Consequently, the zig-zag wall must be invisible. This result is in agreement with the extinction rule of Polcarova et al [18].…”
Section: I-supporting
confidence: 93%
“…As Polcarova and Kaczer [18] first pointed out, the contrast of magnetic walls is mainly due to magnetostriction. Assuming a flat 90° wall : (110) plane which is a coherent twinning boundary between two adjacent domains (I, II) freely deformed by magnetostriction, they showed that for a diffraction vector g so that (MI -M1J.…”
Section: I-mentioning
confidence: 93%
“…The accepted view is that whatever contrast is observed is due to the slight difference in distortion of the various domains (Polcarova  & Kacze  r, 1967;Polcarova  & Gemperlova  , 1969;Schlenker et al, 1968). This difference is associated with the symmetry lowering, which in turn is related to the presence of spontaneous magnetization along the h111i directions in the ferrimagnetic phase of magnetite.…”
Section: Resultsmentioning
confidence: 99%
“…A line focus X-ray tube with Mo anode was used. The beam reflected from the first crystal was limited by slits so as to irradiate a subgrain in the schcxond crystal having a low dislocation density and containing 90" walls fulfilling the visibility rule for the reflection used [2]. The second crystal was rotated thi*ough the reflecting position and the intensity of the reflected beam was measured by a scintillation counter.…”
Section: Experimental Techniquementioning
confidence: 99%
“…The origin of the contrast has been explained on the basis of the magnetostrictive deformation of the crystal [l]. Due to this deformation the crystal lattice of iron is slightly tetragonal and a 90" wall lying in the (110) plane can be considered as a coberent twin boundary [2]. When crossing this wall, some lattice planes change their distance and orientation.…”
Section: Introductionmentioning
confidence: 99%